PEMBUKTIAN UNSUR PERENCANAAN DALAM TINDAK PIDANA PEMBUNUHAN BERENCANA REKONSTRUKSI TEORI DOLUS DAN TINDAK LANJUT IMPLEMENTASI KUHP BARU - Ahiruddin; Siti Humulhaer; Anharyanto; Firmansyah Mahmud; Asri Cahyadi; Oke Wiredarme (CV. Lafadz Jaya, 2026)
This study analyzes the problems of proving the element of premeditation (voorbedachte raad) in the crime of premeditated murder under Article 340 of the Indonesian Criminal Code and Article 459 of Law Number 1 of 2023 concerning the New Criminal Code. The analysis is conducted from the perspective of the theory of intent (dolus) and criminal evidence. The focus of the study lies in the complexity of proving the three requirements of premeditation: (1) the formation of intent in a calm and reflective state, (2) the availability of sufficient time for deliberation, and (3) the execution of the act in a composed state. The research also examines the implications of the enactment of Law Number 1 of 2023 on the formulation and interpretation of premeditated murder. This research employs a normative legal method using statutory, conceptual, and case approaches. The findings indicate that proving the element of premeditation presents significant epistemological challenges due to its subjective and internal nature. As a result, judges often encounter difficulties in determining whether an adequate “period of reflection” existed prior to the commission of the crime. The New Criminal Code retains the fundamental structure of premeditated murder but removes the phrase “intentionally” in the formulation of Article 459, implying that the element of premeditation inherently encompasses intent. This study recommends the development of an expanded theory of dolus informed by criminal neuroscience, as well as the broader use of electronic evidence to demonstrate the existence of premeditation. Furthermore, it highlights the importance of clear evidentiary guidelines within the jurisprudence of the Supreme Court to reduce inconsistencies and disparities in judicial decisions.